Analisa Kerusakan Permukaan Jalan Cipta Karya Kota Pekanbaru Dengan Metode Bina Marga - Baryanto, Tawir; 'Audah, Safridatul; Shalahuddin, Muhammad (Teknik Sipil Universitas Riau, 2025)
Jalan Cipta Karya connects Jalan Bersama and Jalan HR. Soebrantas which is 3.3 km long and 5 m wide. The type of pavement on Jalan Cipta Karya is flexible pavement with the classification of Jalan Cipta Karya including local roads. The aim of this research is to identify the type of damage on Jalan Cipta Karya Pekanbaru City and determine the priority order value of road pavement on Jalan Cipta Karya Pekanbaru City using the Bina Marga method. From the results of research on damage to Jalan Cipta Karya Pekanbaru City STA 00+000 ‒ 02+500, results were obtained that identified the types of damage to Jalan Cipta Karya, namely patches, holes, crocodile skin cracks, longitudinal cracks, transverse cracks. , surface roughness, grooves, and subsidence. From the calculation results, the Priority Order (UP) value for the Pekanbaru City Cipta Karya road pavement was obtained with an average value for the Bina Marga method of 6.44 which is included in the routine maintenance program.